Higher Education in Market-Oriented Socialist Vietnam 2020
DOI: 10.1007/978-3-030-46912-2_4
|View full text |Cite
|
Sign up to set email alerts
|

A Review of University Research Development in Vietnam from 1986 to 2019

Abstract: This paper investigates the impact of breast density distribution on the generalization performance of deep-learning models on mammography images using the VinDr-Mammo dataset. We explore the use of domain adaptation techniques, specifically Domain Adaptive Object Detection (DAOD) with the Noise Latent Transferability Exploration (NLTE) framework, to improve model performance across breast densities under noisy labeling circumstances. We propose a robust augmentation framework to bridge the domain gap between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…A report by the Ministry of Science and Technology showed that the innovation level of private organizations in Vietnam was lesser than expected when compared to that in other countries with similar income per capita; for example, only 53% of Vietnamese innovators informed new products in the market, while this proportion was 75% in Malaysia and 86% in Thailand [ 8 ]. This can be explained by the fact that the majority of private universities are mainly application-oriented universities, which were suitable for career guidance, while there were only few research-oriented universities [ 20 ]. However, currently, many private universities have announced the development of strong research groups with large investments.…”
Section: Discussionmentioning
confidence: 99%
“…A report by the Ministry of Science and Technology showed that the innovation level of private organizations in Vietnam was lesser than expected when compared to that in other countries with similar income per capita; for example, only 53% of Vietnamese innovators informed new products in the market, while this proportion was 75% in Malaysia and 86% in Thailand [ 8 ]. This can be explained by the fact that the majority of private universities are mainly application-oriented universities, which were suitable for career guidance, while there were only few research-oriented universities [ 20 ]. However, currently, many private universities have announced the development of strong research groups with large investments.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the annual book and research allowance paid by the government is meagre and at the same time, a disincentive for increased research output in the universities because; it is paid to all staff regardless of whether they do research or not (Cloete, Maassen & Bailey, 2015). The lack of adequate dedicated funds from which researchers could source for additional funding prevents many Ghanaian researchers from partnering with highly skilled academics across the world for improved research output (Nguyễn, 2014). This indeed has pushed some researchers to rely on local and international donors whose priorities may not be in line with that of the government's.…”
Section: Research Outputmentioning
confidence: 99%
“…Of much importance in recent times, however, is the research and publication output of universities because of their relationship with university visibility, technological innovation and national development (Kruss, McGrath, Petersen & Gastrow, 2015). For example, at the institutional level, research is expected to contribute to institutional visibility while determining the promotion and progression of individuals in academia (Matovu, 2018;Nguyễn, 2014). At the national level, research is seen by many as the key to the economic development of countries especially if it is linked to national goals (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from previous research (Hien, 2010;Nguyen, 2020;Turpin et al, 2015) shows that published articles in social sciences in Vietnam are limited even though this area is believed to play an important role in shaping and constructing human society. Gerke and Evers (2006), for instance, maintain that social science knowledge, as an essential part of the epistemic culture, creates "an image of society and social processes" (p. 8).…”
Section: Introductionmentioning
confidence: 99%